Platelet-to-white blood cell ratio as a predictor of postoperative outcomes in acute type A aortic dissection: a single-center retrospective analysis - Yang, Biwen; Hou, Yucheng; Xu, Mingzhu; Jiang, Tingbo (Frontiers in Cardiovascular Medicine, 2026)
ObjectiveTo evaluate the predictive value of preoperative platelet-to-white blood cell ratio (PWR) for postoperative outcomes in patients with acute type A aortic dissection (ATAAD).MethodsIn this single-center retrospective cohort study, 363 ATAAD patients undergoing emergency type II hybrid aortic arch repair between January 2021 and February 2024 were stratified by median PWR into low PWR (<13.259) and high PWR (≥13.259) groups. Clinical variables, operative details, and outcomes were collected. Primary outcome was in-hospital postoperative adverse events (PAEs) incidence; secondary outcomes included short- and mid-term mortality. Associations were analyzed using multivariable logistic regression and Cox proportional hazards models.ResultsA considerably higher incidence of PAEs was observed in the low PWR (<13.259) relative to the high PWR (41.99% vs. 21.43%, p < 0.001) groups. Moreover, patients with low PWR showed increased in-hospital (13.81% vs. 3.30%, p = 0.001), 90-day (14.36% vs. 4.40%, p < 0.001), and 1-year (16.38% vs. 5.56%, p = 0.001) mortalities. Multivariable logistic regression detected low preoperative PWR as a distinct marker of PAEs. The areas under the curve for PWR in estimating PAEs was 0.705 (95% CI, 0.649–0.760). Cox regression analysis confirmed a significant association between low PWR and elevated short- and mid-term mortality.ConclusionPreoperative low PWR independently predicts postoperative complications and mortality in ATAAD patients, serving as an accessible and cost-effective biomarker for risk stratification and clinical decision-making.